Digital Congregation News Android-Based in The Christian Evangelical Church in Minahasa - Heilbert Armando Mapaly; Salaki Reynaldo Joshua; Salvius Paulus Lengkong (Journal of Engineering, Electrical and Informatics, 2023)
Information is a necessity that is needed by everyone. With the devel-opment of Information Technology today, it is very helpful for people to get the desired information easily and quickly. This digital media pro-vides a number of advantages when compared to print media. One of the advantages of this digital media that is very pronounced is that this digital media can reduce printing costs, because this digital media does not need to be printed, but only uses internet media to disseminate the information. In church activities, also cannot be separated from the delivery of information to the church congregation. The purpose of this study is to develop an android-based mobile software to be able to pro-vide information or congregational news digitally. In this research, a number of stages will be carried out, namely Literature Study, Data Col-lection, System Design and Data Model, System Development and Data Processing, Testing and Evaluation, Reporting and Publication. This research produces a mobile application that can be used to provide news information to the congregation.